Drug interactions for elderly people with mental and behavioral disorders: a systematic scoping review - Forgerini, Marcela [UNESP]; Schiavo, Geovana [UNESP]; Lucchetta, Rosa Camila [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (Elsevier, 2021)
Objectives: To identify drug interactions of potentially inappropriate medications and mental and behavioral disorders, according to explicit potentially inappropriate medications criteria-based tools. Methodology: A systematic scoping review was conducted in February 2020. Study characteristics, potentially inappropriate medications, drug interactions, rationale, and therapeutic management proposed were extracted. The commercialization and potentially inappropriate medications standard as essential in Brazil and in the world were identified. Therapeutic management was proposed for the most cited potentially inappropriate medications. Results: 36 tools including 151 drug interactions, in addition to 132 potentially inappropriate medications with concerns related to six mental and behavioral disorders were identified. Cognitive impairment and dementia were the most frequently disorders reported and antipsychotics, anticholinergics, and benzodiazepines were the pharmacological classes more involved in the drug interactions. Despite the tools recommended risperidone and quetiapine when the use of antipsychotics were inevitable; levodopa + carbidopa for Parkinson's disease; and short and intermediate half-life benzodiazepines; the quality of the evidence needs to be assessed. In this review, sleep hygiene; deprescription; medication review; and clinical monitoring of adverse drug reactions are strongly recommended. In addition, to consider agomelatine, bupropion, moclobemide and melatonin as potential safer options for benzodiazepines. Conclusion: Knowing the clinical conditions or risk morbidities associated with the use of potentially inappropriate medications and management of these medications for safer therapeutic equivalents or non-pharmacotherapeutic alternatives are relevant for patient safety.
Keywords: Aged; Contraindications; Drug; Drug-Related Effects and Adverse Reactions; Inappropriate Prescribing; Medications Errors; Prescription Drug Misuse